2004
DOI: 10.1007/s00253-004-1623-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation pathways of cyclic alkanes in Rhodococcus sp. NDKK48

Abstract: The degradation pathways for cyclic alkanes (c-alkanes) in Rhodococcus sp. NDKK48 were investigated. Strain NDKK48 used dodecylcyclohexane as a sole carbon and energy source, and five metabolites in the dodecylcyclohexane degradation pathway were detected by gas-chromatography/mass spectra. The metabolites were identified as cyclohexanecarboxylic acid, cyclohexylacetic acid, 1-cyclohexene-1-acetic acid, 4-dodecylcyclohexanol, and 4-dodecylcyclohexanone. The strain degrades dodecylcyclohexane via a ring oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…This strain did degrade c-alkanes under limited conditions, such as co-metabolism with n-alkanes (Koma et al 2003a). On the other hand, strains NDKK48 and NDKY76A used n-alkanes and c-alkanes as sole carbon and energy sources (Koma et al 2003b), but the metabolic pathways for c-alkanes differed between the two strains (Koma et al 2003a(Koma et al , 2005. Since the hydrocarbon-degrading abilities seem to differ among genera, exhaustive analyses of hydrocarbon-degradation will be important for selecting microorganisms for bioremediation of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…This strain did degrade c-alkanes under limited conditions, such as co-metabolism with n-alkanes (Koma et al 2003a). On the other hand, strains NDKK48 and NDKY76A used n-alkanes and c-alkanes as sole carbon and energy sources (Koma et al 2003b), but the metabolic pathways for c-alkanes differed between the two strains (Koma et al 2003a(Koma et al , 2005. Since the hydrocarbon-degrading abilities seem to differ among genera, exhaustive analyses of hydrocarbon-degradation will be important for selecting microorganisms for bioremediation of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…the aromatization; THF to furan via 2,3-hydrofuran and lactone formation, ring-cleavage of THF via tetrahydrofuran-2-ol and gamma-butyrolactione [13]. Previously aromatization of cyclic alkanes has been reported in limited number of studies; by aerobic bacteria [7], by denitrifying bacteria [6], and by animal liver cells [14].…”
Section: Degradation Pathway Of Cyclohexane and Metabolitesmentioning
confidence: 99%
“…Generally, aromatization plays an important role in the biosynthesis of aromatic amino acids and lignin and estrogen. Although the involvement of aromatization in biodegradation is uncommon, in limited number of studies, biodegradation of cyclic alkanes have been reported by aromatization in aerobic bacteria [6]. Kaneda [7] also reported that Corynebacterium cyclohexanicum degraded cyclohexanecarboxylic acid through the aromatization.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Additionally, BVMO’s are known to be responsible for pro-drug activation (3) as well as biodegradation reactions. (4-6)…”
mentioning
confidence: 99%